2010
DOI: 10.1080/01411920902989219
|View full text |Cite
|
Sign up to set email alerts
|

‘To benefit the world by whatever means possible’: Adolescents' constructed meanings for global citizenship

Abstract: This article reports on the ways that 77 students in an international studies programme constructed meanings for global citizenship. The focus was on their personal meanings for the topic and how they articulated a global identity with their national civic beliefs. Data were collected from online discussion boards, written essays and 20 interviews. A key finding was that the students' political language for global citizenship, examined here in terms of purpose, membership and relationship with national citizen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 29 publications
2
30
0
5
Order By: Relevance
“…A few exceptions stand out. First, Myers (2010) provides a fruitful discussion in documenting the discursive understanding of global citizenship of students in Pennsylvania through a series of in-depth interviews, bringing out the dispute about whether or not global citizenship is innate (i.e., membership belongs to all humans) or acquired, whether it is a moral commitment or a legal status, and whether or not it is compatible with national citizenship. Roudometof (2005) took note of this tension early on in his discussion on "rooted cosmopolitanism", where global and local are seen as reconcilable through the emergence of "glocalization" as an expression of manifestations of the global in the context of the local (Robertson, 1994).…”
Section: Measuring Globalization and Global Citizenship In Hong Kongmentioning
confidence: 99%
“…A few exceptions stand out. First, Myers (2010) provides a fruitful discussion in documenting the discursive understanding of global citizenship of students in Pennsylvania through a series of in-depth interviews, bringing out the dispute about whether or not global citizenship is innate (i.e., membership belongs to all humans) or acquired, whether it is a moral commitment or a legal status, and whether or not it is compatible with national citizenship. Roudometof (2005) took note of this tension early on in his discussion on "rooted cosmopolitanism", where global and local are seen as reconcilable through the emergence of "glocalization" as an expression of manifestations of the global in the context of the local (Robertson, 1994).…”
Section: Measuring Globalization and Global Citizenship In Hong Kongmentioning
confidence: 99%
“…Studies of global citizenship education have found that teachers in the United States, compared to their colleagues in Canada, Western Europe, and Southeast Asia, are less enthusiastic about teaching global citizenship and prefer a national model (Myers, 2010 Harshman and Augustine Rapoport, 2010). Building on these fi ndings, a study to understand how teachers in Indiana conceptualize and teach about global citizenship found that teachers tend to rationalize the unfamiliar concepts of global citizenship through more familiar concepts related to national citizenship (Rapoport, 2010).…”
Section: Improving the Place Of Online Discussion Forums In Global CImentioning
confidence: 95%
“…I would suggest that Myers' (2010) findings are representative of my earlier points concerning the separation of cosmopolitan ideals and the implementation of global citizenship as a concept. Firstly, Myers' study reinforces the case that there is a disjuncture between what is national and what is global.…”
mentioning
confidence: 77%
“…As a result of this, Myers (2010) argues that whilst a global awareness has the ability to enhance our moral outlook towards the world as a whole, it is potentially divisive with regard to our local, national and cultural affiliations. Myers interviewed 77 adolescent students about their views of global citizenship, which they were taught within an international school in the United States.…”
mentioning
confidence: 99%